Integrated commodities in the digital economy. (May 2020) - Athique, Adrian
At the heart of the digital economy is the willful imposition of a powerful combination of hardware and software, time and data, surveillance, prediction and behavourial control. This article argues that a central ambition of digital society has been the pursuit of an integrated commodity form. The novelty of this integrated commodity stems not only from the convergence of production and consumption but also from the subsumption of sociability itself. As a consequence, we are required to consider all social actions within digital society as being transactions enshrined within an economy of integrated markets. Our acceptance of these new commodity relations is paving the way for a 'great integration' of simultaneous transactions across different social domains. Borrowing from Karl Polanyi's account of an earlier transformation, this article will propose that the prerequisites of digital society and the integrated commodity form have been established through the constitution of a series of 'fictitious commodities'.